THE IMPACT OF PHYSICAL EDUCATION ON MENTAL HEALTH: A COMPREHENSIVE ANALYSIS (International Journal of Food and Nutritional Sciences, 2023)
This research paper explores the relationship between physical education (PE) programs and mental health, focusing on how regular physical activity within the school environment influences students' psychological well-being. Through a review of existing literature and research studies, this paper highlights the benefits of PE on stress reduction, anxiety management, mood enhancement, and cognitive function. Additionally, the study explores potential mechanisms through which physical activity promotes mental health, including the release of endorphins, social engagement, and the development of coping skills. The paper concludes by discussing the implications for curriculum development and mental health initiatives in schools.